Porosity of sediment cores during SONNE cruises SO268/1 and SO268/2 - Matthias Haeckel (PANGAEA, 2024)
This dataset comprises measurements of porosity from sediment cores (GC, MUC, ROV-operated PUC) retrieved in polymetallic nodule areas of the Clarion-Clipperton-Zone, NE Pacific. The research was carried out in the framework of the European collaborative JPI Oceans project MiningImpact onboard RV SONNE cruise SO268 in February-May 2019 to collect environmental baseline data prior to a nodule collector test in the German (BGR) and Belgian (GSR) contract areas for polymetallic nodule exploration. Wet sediment samples were subsampled in tightly closed pre-weighed plastic vessels. Water content of the samples was determined by weight difference before and after freeze-drying. Conversion to volume fraction of porewater in the sediment (porosity) assumed a water density of 1.023 g/cm3 and a dry sediment density of 2.5 g/cm3. Salt-correction assumed a salinity of 35.